Feasibility of creating a normative database of colour Doppler imaging parameters in glaucomatous eyes and controls. Issue 9 (24th November 2010) - Rusia, Deepam; Harris, Alon; Pernic, Allison; Williamson, Kathleen M; Moss, Adam M; Shoshani, Yochai Z; Siesky, Brent
Abstract : Background and aims: Colour Doppler imaging (CDI) is a frequently cited methodology for quantifying ocular blood flow velocities. This investigation reviews the feasibility of creating a normative database of CDI parameters in glaucoma patients and controls. A literature search was conducted for CDI studies involving glaucomatous eyes. Using data from these studies, a weighted mean was derived for the peak systolic velocity, end diastolic velocity and Pourcelot's resistive index in the ophthalmic, central retinal and posterior ciliary arteries. A multivariate analysis was performed to identify whether methodological characteristics contributed to the inter-study variance in CDI values. Data from 3061 glaucoma patients and 1072 controls were included. The mean values for glaucomatous eyes were within one standard deviation of the values for controls for most CDI parameters. Gender mix (p=0.043), intraocular pressure status (p=0.017), frequency of the ultrasound transducer (p=0.02) and whether the patients were on antihypertensive therapy (p=0.004) contributed to the variance. Methodological differences create inter-study variance in CDI values, complicating the construction of a normative database and limiting its utility. Because the mean values for glaucomatous and normal eyes have overlapping ranges, caution should be used when classifying glaucoma status based on a single CDI measurement.